2018
DOI: 10.3390/en11123340
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Disturbance Decoupling Control for Hydro-Turbine Governing System with Sloping Ceiling Tailrace Tunnel Based on Differential Geometry Theory

Abstract: For hydropower stations with sloping ceiling tailrace tunnel (SCTT), the regulation quality of hydro-turbine governing system (HTGS) under the proportional-integral-derivative (PID) strategy is poor. In order to improve the regulation quality of HTGS, the nonlinear disturbance decoupling control (NDDC) based on differential geometry theory is firstly applied into the HTGS with SCTT. The rigorous and complete construction method of nominal output function is proposed. Based on the obtained nominal output functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…A comparison between the regulation quality of the NSF control strategy and the PID strategy ( Figure 27) indicated that the dynamic performance and response speed under the former were obviously better than those under the latter. In Reference [46], Guo studied another nonlinear control strategy, i.e., a nonlinear disturbance decoupling control (NDDC) strategy, for HTGSes with SCTTs. The theoretical basis of the NDDC strategy is differential geometry theory.…”
Section: Transient Process Control Of Htgses With Scttsmentioning
confidence: 99%
See 3 more Smart Citations
“…A comparison between the regulation quality of the NSF control strategy and the PID strategy ( Figure 27) indicated that the dynamic performance and response speed under the former were obviously better than those under the latter. In Reference [46], Guo studied another nonlinear control strategy, i.e., a nonlinear disturbance decoupling control (NDDC) strategy, for HTGSes with SCTTs. The theoretical basis of the NDDC strategy is differential geometry theory.…”
Section: Transient Process Control Of Htgses With Scttsmentioning
confidence: 99%
“…In terms of Issue 6, it is discussed in References [45][46][47][48][49][50][51][52]. The control of transient processes relates to the regulation quality of hydropower plants with SCTTs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the hydraulic turbine governing system (HTGS), as the key structure of any hydropower plant, is finely studied and designed to guarantee the operation's safety and proper response [4]. However, the essences of HTGS are nonlinear characteristic, time-variant and a non-minimum phase system, which require efforts on precise and effective studies on practical control strategy design [5][6][7]. To overcome the obstacles in nonlinear plant controlling, considerable interests and research in the applications of HTGS regulating technique have been raised in the past several decades, such as fractional-PID control [8], fuzzy control [9], predictive control [10], adaptive control [11] and synergetic control [6,12].…”
Section: Introductionmentioning
confidence: 99%